Acute fibrinous and organizing pneumonia induced by cat scratch disease: a first case report - Yang, Zhen; Li, Zhenhua; Geng, Shuang; Ni, Jixiang; Hu, Hongling (Frontiers in Medicine, 2025)
We describe the first documented case of acute fibrinous and organizing pneumonia (AFOP) induced by cat-scratch disease (CSD). A 74-year-old female patient was admitted to the hospital with progressive dyspnea and dry cough for more than 1 month that did not respond to conventional antibiotic therapy. Physical examination revealed cat bite scars on the left index finger. Chest computed tomography (CT) revealed bilateral diffuse ground-glass opacities and consolidation. Percutaneous lung biopsy pathology confirmed the characteristic changes of AFOP, including fibrin ‘ball ‘formation in the alveolar cavity with organizing pneumonia. Polymerase chain reaction (PCR) testing was positive for Bartonella henselae; other pathogens and autoimmune diseases were excluded. Following treatment with doxycycline and corticosteroids, the patient exhibited clinical and radiographic improvement. This case reveals the pathogenic association between CSD and AFOP for the first time, expanding the infectious etiology spectrum of AFOP and revealing the potential association between rare infections and special types of interstitial pneumonia, providing a new perspective for differential clinical diagnoses.